Analysis of Groyne Placement on Minimising River Bank Erosion. (2016) - Krishna Prasad, S.; Indulekha, K.P.; Balan, K.
Abstract: Bank erosion is the wearing away of the banks of a stream or river. Impacts of river bank erosion are multifarious: social, economic, health, education and sometimes political. Groynes are structures constructed in rivers to protect the shore. Groynes are generally made of wood, concrete, or rock piles etc. In the present study coir geotextiles in the form of cocologs are used as the groynes to make the groyne more ecofriendly. Study mainly concentrates on analysing the effects of placing groynes at different angles from 45 0 to 135 0 and to find the most effective arrangement for minimising the erosion. Results indicate that cocolog-groynes are effective in minimizing the erosion and protecting the bank. Maximum protection is observed for groyne angle of 135 0 .